RANCANG BANGUN SISTEM KENDALI PENANAMAN TUMBUHAN HORTIKULTURA DI DALAM RUANGAN TERTUTUP - Jumiyatun Jumiyatun; Ardi Amir; Rachmiati Ndobe; Supriyadi Supriyadi (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2019)
The aim from this research is to design a device who can make grow and fash horticultural plant in inside a room without side-effect of sun-light with arduino mega as the brain who had control all of the system with the power for monitoring and control the light, temperature of the room, soil damp and watering the plans. Subtitute the sun-light for photosinthesis process exploit LED grow light is red and blue color, while for temperature detection inside the room used temperature sensor DHT22,chiller as a freeze tool and for detection a sum soil damp less than 280, the motor pump will active for doing watering the plans.Lettuce-plan and leady vegetable who has product from different system appropriate with combination/domination ligh who has already used, for lettuce-plan dominate with blue light and dominan red light produce lettuce is not good enough while for light combination blue and red, lettuce-plan who has produce looking good, the are many leaf-sum, is nit brittle, and growth very fast. For leafy vegetable from three combination/dominate light who used for produce in the same condition is growth very fast, has tall stem, and small, the less leafe sum (distance) and the leave color is yelow.